⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ x + 7 y + 3 v + 5 u = 1 6 8 x + 4 y + 6 v + 2 u = − 1 6 2 x + 6 y + 4 v + 8 u = 1 6 5 x + 3 y + 7 v + u = − 1 6
Real numbers x , y , u , and v satisfy the system of equations above. Find x y u v .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution
Did the exact same...
Same way..
Easiest method!
Put the left half of the equation into a matrix (not the variables, the coefficients) (4 by 4), take the inverse, then put the right half into a matrix (4 by 1) and multiply the two together. You will get a matrix (4 by 1) where the top number is x, the next is y... (in the future order try appear in the equations). You should have 2, -2, 2, -2. Multiplied together, it is 16.
This sounds complicated, but once you understand it and you use a calculator, it is quite simple. In fact, I did this on my phone! (So sorry if there are typos in this solution!)
nice! .... 1 up vote
To be honest, mate. I don't know why the two solutions above yours don't use the easy way. Maybe because they have never heard what a matrix is..... :(
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ x + 7 y + 3 v + 5 u = 1 6 8 x + 4 y + 6 v + 2 u = − 1 6 2 x + 6 y + 4 v + 8 u = 1 6 5 x + 3 y + 7 v + u = − 1 6 . . . ( 1 ) . . . ( 2 ) . . . ( 3 ) . . . ( 4 )
( 1 ) + ( 2 ) : ( 3 ) + ( 4 ) : ( 3 ) − ( 1 ) : ( 2 ) − ( 4 ) : 9 x + 1 1 y + 9 v + 7 u 7 x + 9 y + 1 1 v + 9 u x − y + v + 3 u 3 x + y − v + u = 0 = 0 = 0 = 0 . . . ( 5 ) . . . ( 6 ) . . . ( 7 ) . . . ( 8 )
( 7 ) + ( 8 ) : 4 x + 4 u ⟹ x = 0 = − u
( 5 ) + ( 6 ) : 1 6 x + 2 0 y + 2 0 v + 1 6 u 2 0 y + 2 0 v ⟹ y = 0 = 0 = − v
( 8 ) : 3 x + y − v + u 3 x + y + y − x 2 x + 2 y ⟹ x = 0 = 0 = 0 = − y = v = − u
( 1 ) : x + 7 y + 3 v + 5 u x − 7 x + 3 x − 5 x − 8 x ⟹ x = 1 6 = 1 6 = 1 6 = − 2
⟹ x = − 2 , y = 2 , v = − 2 , u = 2 , ⟹ x y u v = 1 6
Nice! I spent so long writing that out I had no idea someone else was doing it for me!
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ x + 7 y + 3 v + 5 u = 1 6 8 x + 4 y + 6 v + 2 u = − 1 6 2 x + 6 y + 4 v + 8 u = 1 6 5 x + 3 y + 7 v + u = − 1 6
Real numbers x , y , u , and v satisfy the system of equations above. Find x y u v .
Eq 1 + Eq 4
= 6 x + 10 y + 10 v + 6 u = 0
Eq 2 + Eq 3
= 10 x + 10 y + 10 v + 10 u = 0
From this we obtain
6 ( x + u ) + 10 ( y + v ) = 0
10 ( x + u ) + 10 ( y + v ) = 0
which yields x + u = 0 and y + v = 0.
Substituting - x for u , and − y for v in the original equation, we find
− 4 x + 4 y = 16
6 x − 2 y = -16
2 x + 2 y = 0
Plugging this in with earlier assumptions we find
x = -2, y = 2, u = 2, v = -2
x y u v = 16
Good approach exploiting the symmetry, which makes solving the system of linear equations less tedious.
Typo: 6 x + 1 0 y + 1 0 v + 6 u = 0
You can also solve this using a matrix (4X4 matrices are tedious to invert by hand but a computer makes short work of it).
you can solve it using matrix multiplication, A ∗ B = C then B = A − 1 ∗ C were A is the coefficients matrix, B is the variables matrix, and C is the results matrix. see https: //www.mathsisfun.com/algebra/systems-linear-equations-matrices.html for further explanation.
Problem Loading...
Note Loading...
Set Loading...
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ x + 7 y + 3 v + 5 u = 1 6 8 x + 4 y + 6 v + 2 u = − 1 6 2 x + 6 y + 4 v + 8 u = 1 6 5 x + 3 y + 7 v + 1 u = − 1 6 ⟹ 1 ⟹ 2 ⟹ 3 ⟹ 4
1 + 4 :
6 x + 1 0 y + 1 0 v + 6 u = 0 ⟹ 5
2 + 3 :
1 0 x + 1 0 y + 1 0 v + 1 0 u = 0 ⟹ 6
6 − 5 :
4 x + 4 u = 0 x + u = 0 ⟹ 7 x = − u ⟹ 8
Substitute 7 into 5 :
6 ( x + u ) + 1 0 ( y + v ) = 0 1 0 ( y + v ) = 0 y + v = 0 v = − y ⟹ 9
Substitute 8 and 9 into 1 :
− u + 7 y + 3 ( − y ) + 5 u = 1 6 4 u + 4 y = 1 6 u + y = 4 ⟹ 1 0
Substitute 8 and 9 into 3 :
2 ( − u ) + 6 y + 4 ( − y ) + 8 u = 1 6 6 u + 2 y = 1 6 3 u + y = 8 ⟹ 1 1
1 1 − 1 0 :
2 u = 4 ⟹ u = 2 2 + y = 4 ⟹ y = 2 v = − y = − 2 x = − u = − 2
Therefore, x y u v = − 2 ( 2 ) ( 2 ) ( − 2 ) = 1 6